The growth of brightest cluster galaxies and intracluster light over the past 10 billion years. Issue 3 (23rd November 2019) - DeMaio, Tahlia; Gonzalez, Anthony H; Zabludoff, Ann; Zaritsky, Dennis; Aldering, Greg; Brodwin, Mark; Connor, Thomas; Donahue, Megan; Hayden, Brian; Mulchaey, John S; Perlmutter, Saul; Stanford, S A
ABSTRACT: We constrain the evolution of the brightest cluster galaxy plus intracluster light (BCG + ICL) using an ensemble of 42 galaxy groups and clusters that span redshifts of z = 0.05−1.75 and masses of M500, c = 2 × 10 13 −10 15 M⊙ . Specifically, we measure the relationship between the BCG + ICL stellar mass M⋆ and M500, c at projected radii 10 < r < 100 kpc for three different epochs. At intermediate redshift (z=0.40 ), where we have the best data, we find M⋆ ∝ M500, c 0.48 ± 0.06 . Fixing the exponent of this power law for all redshifts, we constrain the normalization of this relation to be 2.08 ± 0.21 times higher at z=0.40 than at high redshift (z=1.55 ). We find no change in the relation from intermediate to low redshift (z=0.10 ). In other words, for fixed M500, c, M⋆ at 10 < r < 100 kpc increases from z=1.55 to z=0.40 and not significantly thereafter. Theoretical models predict that the physical mass growth of the cluster from z = 1.5 to z = 0 within r500, c is 1.4×, excluding evolution due to definition of r500, c . We find that M⋆ within the central 100 kpc increases by ∼3.8× over the same period. Thus, the growth of M⋆ in this central region is more than a factor of 2 greater than the physical mass growth of the cluster as a whole. Furthermore, the concentration of the BCG + ICL stellar mass, defined by the ratio of stellar mass within 10 kpc to the total stellar mass within 100 kpc, decreases with increasing M500, c at all z . We interpret this result as evidence for inside–out growth of the BCG + ICL over the past 10 Gyr, with stellar mass assembly occurring at larger radii at later times.